Medical on-call handbook for foundation doctors: a quality improvement project at Barts Health NHS Trust, London, UK - Carola Maria Bigogno; Francesca Bladt; Amy Edwards; Priyanka Sivakumaran; Lamin King (Future Healthcare Journal)
Background: Newly qualified doctors face numerous challenges when they transition from medical school to the Foundation program, often feeling unprepared to face the several duties and responsibilities of their role.1 This issue is most evident during busy medicine on-call shifts in large district general hospitals, where Foundation Year 1 (FY1) doctors are expected to manage handovers, bleeps and medical emergencies with limited prior experience and support. Moreover, previous research has also highlighted a common lack of confidence among new FY1 doctors when making clinical decisions and managing deteriorating patients.1 This project aimed to improve confidence and knowledge among newly qualified doctors, through a structured on-call handbook discussing common medical presentations and emergencies. Methods: A comprehensive Medical On-Call Handbook was developed in collaboration with senior registrars and consultants, covering common emergencies, such as cardiac events, drowsy patients, haematuria and neurological symptoms, providing structured guidance on initial assessment and management, as well as the role of FY1 doctors during medical emergencies. To evaluate the change in confidence in managing common emergencies, a survey was conducted before and after the review of the handbook among FY1 doctors at Barts Health NHS Trust, assessing confidence levels, overall and across specific medical scenarios. Results: The pre-handbook survey data revealed that a significant proportion of FY1 doctors felt unfamiliar with their responsibilities and lacked confidence in managing common medical emergencies (n=22, Fig 1). These findings are in keeping with previous work showing reduced confidence of FY1 doctors in handling emergencies, prescribing and making clinical decisions.2 The post-handbook survey data revealed that all surveyed FY1 doctors found the handbook useful in addressing common emergencies. The average confidence increase in handling medical emergencies was 72%, with the greatest improvement observed in conducting comfort reviews and understanding the FY1’s role during medical emergency team (MET) and cardiac arrest calls (n=5, Fig 2). These findings are consistent with prior research highlighting the effectiveness of structured educational resources in improving junior doctors’ confidence and clinical preparedness.3,4 In addition, feedback indicated that, while the handbook was beneficial for common on-call scenarios, some complex topics, such as electrolyte disturbances, shortness of breath, melaena, vomiting and delirium, might be better suited for structured teaching sessions. Conclusion: This quality improvement project demonstrated that a structured on-call handbook can significantly support and enhance FY1 doctors' confidence in managing emergencies, directly contributing to improved patient care and safety.5 Given its success, future developments will focus on creating a mobile app for easy accessibility, tailoring handbooks to specific hospital sites within the trust (Royal London Hospital, St Bartholomew’s, Newham University Hospital and Whipps Cross Hospital), and supplementing learning with a YouTube teaching series for more complex topics. These findings support the wider recommendations by the General Medical Council regarding the importance of structured educational interventions to support newly qualified doctors.3